Virtualization of the Paint Mixing Process Using the Hardware in the Loop Technique - Toapanta, Kelvin (2024)
This paper describes the implementation of the Hardware in the Loop technique, which in the automation area allows communication between a simulated industrial process (software) and a programmable logic controller, PLC, (Hardware). The simulation section consists of TIA PORTAL for the automation of the paint mixing process, while the visualization and monitoring corresponding to the SCADA system is done with the INTOUCH software, and finally the virtualization is done in the Unity 3D software, in order to provide greater realism to the user in the manipulation of the variables that make up the process. The simulations consist of a bilateral communication between INTOUCH and TIA Portal software through tags created in KepServer of the respective variables for the control and monitoring of the process. While the communication with Unity 3D and TIA Portal software will be done through a free Sharp7 library. By means of data blocks, the TIA Portal programming will be related to the variables created in Visual Studio. This will be connected to a real control panel, consisting of a Siemens S7–1200 PLC through the open communication protocol that allows the exchange of data via Industrial Ethernet with TCP/IP protocol (Server–Client), obtaining a digital data sent stored in bits. The Ethernet information frame with a delay time of 220 ms which is considered optimal within the response of an industrial process.